Corporate Governance, Capital Expenditure Dan Cash Holdings - Yanti; Liana Susanto; Henny Wirianata; Viriany (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2019)
This study aims to obtain empirical evidence about the effect of Corporate Governance and Capital Expenditure on Cash Holding. This study uses secondary data from financial statements of manufacturing companies listed on the Indonesia Stock Exchange in 2014-2016. The structure of Corporate Governance is measured using independent commissioners, board of commissioners, and institutional ownership. The analytical method used in this study is multiple regression analysis which is processed with the E-Views program. The results of this study indicate that independent commissioners, the board size, and institutional ownership partially have no significant effect on cash holding. While Capital Expenditure has a significant and negative effect on cash holding.